Analysis Of Socio-Economic Changes On The Welfare Of Corn Farmers In The Donggo Community - Baharudin Baharudin; Siti Rahmawati (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The socio-economic changes occurring in the agricultural sector have a significant impact on the welfare of farmers. These changes include shifts in production patterns, fluctuations in agricultural prices, rising production costs, and changes in the social structure of rural communities. This situation requires farmers to adapt in order to sustain their livelihoods and improve their family's welfare. This study aims to analyze socio-economic changes and their impact on farmers' welfare. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that socio-economic changes have a dual impact on farmers' welfare. On one hand, innovations and modernization in agriculture have the potential to increase productivity, but on the other hand, limited access to capital, technology, and markets prevents farmers' welfare from improving optimally. Therefore, active involvement of the government and relevant institutions is needed to support farmers' empowerment through favorable policies, strengthening farmers' institutions, and increasing access to production resources to achieve sustainable farmers' welfare.